Active Covid-19 infection and transmission after the first dose of the BNT162b2 mRNA vaccination in Saudi Arabia: A case report - Asem A. Allam; Anwar A. Sayed (Elsevier, 2021)
A 47-year-old non-smoker male who has received the first dose of the BNT162b2 mRNA Covid-19 vaccine in Saudi Arabia. At day 3 post-vaccination, he tested negative for Covid-19 and travelled to Egypt. On day 12 he developed runny nose, body ache and fever, and he reportedly tested (PCR) negative for Covid-19 Upon his return to Saudi on day 15, his symptoms have worsened and he presented to the Emergency Department, at which he tested positive for Covid-19. The patient was overweight (BMI = 29), was not suffering from any comorbidities and was not taking any medication. Upon examination, he was vitally stable and his laboratory investigation only revealed a slightly increased Creatinine. His chest X-ray was unremarkable.His condition did not require hospital admission, so he was discharged and advised to home-isolate himself. Four days after his discharge, his entire household came to the hospital and tested positive for Covid-19.This is the first case report, in Saudi Arabia, of a person receiving the first dose of the BNT162b2 vaccine and got infected with Covid-19 afterwards. The report highlights the significance of receiving the second dose of the vaccine to be effective. It also demonstrates that those with a single dose mRNA vaccine, could get infected and transmit the infection.